A new species of Catomus Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from the Aeolian archipelago (Sicily, Italy) - Ponel, Philippe; Cascio, Pietro Lo; Soldati, Fabien (Zootaxa, 2020)
Catomus aeolicus sp. nov. is described from the Aeolian archipelago (Sicily, Italy). The new species differs from the other European Catomus by having distinctly bent tibiae, longer antennae (especially in males), and strongly highlighted sexual dimorphism. The shape of the aedeagus also seems diagnostic for this new species.